Strategi Komunikasi Internal Organisasi PT Fajar Mekar Indah dalam Memberdayakan Kompetensi Karyawan - Annisa Catur Sheilawati; Robbikal Muntaha Meliala; George Wilhelm Bender (Cerdika: Jurnal Ilmiah Indonesia, 2025)
This study focuses on the importance of internal communication strategies at PT Fajar Mekar Indah in empowering employee competencies, particularly within the housekeeping division, in facing the increasingly competitive business environment. Effective internal communication plays a crucial role in enhancing employees' skills and productivity. The objectives of this research are: (1) to descriptively examine and explain how the internal communication strategy implemented at PT Fajar Mekar Indah empowers employee competencies, and (2) to evaluate the training provided to employees in 2024. This study uses a qualitative analysis method with a SWOT analysis approach. Data were collected through interviews with Key Informants and analyzed to portray the company's internal communication condition. The findings indicate that while internal communication at PT Fajar Mekar Indah is well-organized, the implementation of the Smile, Greet, Say Hello, Be Courteous, and Be Respectful (5S) values remains a challenge that affects employee relations. SOP training programs and compensation have been implemented, but the evaluation of 5S application is still lacking. Based on the SWOT analysis, strengths lie in the well-organized communication structure, while weaknesses include the lack of evaluation of work culture. Opportunities to enhance interpersonal training programs and ethical work practices are open, while threats such as potential communication conflicts across levels need to be managed with appropriate strategies. The integration of internal communication strategies, along with improvements in 5S implementation, is expected to enhance employee competencies and operational efficiency within the company.